The Influence of Compensation, Leadership, and Competency on the Performance Employees Through Motivation as a Mediating Variable - Nurul Fadhlya Hidayatunnisa; R. Adjeng Mariana F (Dinasti International Journal of Education Management And Social Science, 2024)
This research examines the influence of compensation, leadership, and competence on the performance of employees through motivation as a mediating variable. The research method used is quantitative with a descriptive verification approach. Researchers use nonprobability sampling techniques, namely sampling techniques that do not provide opportunities or opportunities for each member of the population to be selected as a sample. For this study, a sample of the entire employee population of 120 people was selected. The tool used to analyze data in this research is SmartPLS 4 2024. The research results show that (1) Compensation has a positive effect on motivation, (2) Leadership has a positive effect on motivation, (3) Competency has a positive effect on motivation, (4) Compensation has no positive effect on employee performance, (5) Leadership has no positive effect on employee performance (6) Competence on performance has a positive effect on employee performance (7) Motivation has a positive effect on employee performance, (8) Compensation has a positive effect on performance through motivation, (9) Leadership has a positive effect on performance through motivation, (10) Competence has a positive effect on performance positive impact on performance through motivation.